How to monitor and discriminate the causes of lower limb swelling during home-based rehabilitation after total knee arthroplasty? A delphi study - Lin Yang; Hui-Wu Li; Zan-Jing Zhai; Cai-Feng Wang; Bei-Ying Wu; Jia Zhou; Wei-Wei Bian; Hong Ruan (Arthroplasty)
Abstract Purpose Swelling in the lower limbs after total knee arthroplasty (TKA) affects surgical outcomes. Prolonged swelling requires monitoring and remote management during home-based rehabilitation. Causes of swelling vary but, so far, no indicators are available to monitor and identify causes of lower limb swelling, making it difficult to implement targeted interventions. This study aimed to find the indicators to monitor and identify the causes of lower limb swelling during home-based rehabilitation after TKA by literature research and consulting experts from various disciplines. Methods The Delphi method was used. Based on literature research and analysis, a set of candidate indicators was developed. Fifteen experts from different disciplines evaluated the validity of the indicators and provided modification suggestions. Results After two rounds of Delphi consultations, consensus was reached. Agreement scores ranged from 4.40 to 5.00, with low variability (standard deviation 0.00–0.91) and high consistency (coefficient of variation 0.00–0.20). P was less than 0.05 in Kendall’s W with an agreement rate of 80.00–100%. In the final set of indicators, there were five primary indicators (representing four swelling causes and a general category), along with 23 secondary indicators and 40 tertiary indicators. Conclusions This study preliminarily established indicators for at-home identification of post-TKA swelling caused by four distinct reasons. Further research is needed to validate the value of these indicators in distinguishing the causes of swelling.